Factors Involved in the Digital Identity of a University Student: An Exploratory Analysis - Félix Aragundi, Leyla Paola; Bravo Félix, Salma; Villacis Molina, Héctor Gerardo (Revista Universidad de Guayaquil, 2024)
The digital identity of a university student has become a relevant issue in the current educational environment, where online presence plays a fundamental role in the academic and social life of all people. This article aims to explore the factors involved in the construction and development of the digital identity of university students. An exploratory analysis is carried out based on a review of the existing scientific and technical literature, in order to understand the key aspects related to digital identity and offer recommendations for its effective management.
Keywords: higher education; digital competence; digital identity